Kant and the Metaphysics of Causality - Eric Watskin (Cambridge University Press, 2005)

(untitled)
The goal of this book is to present a comprehensive account of Kantâ€™s viewsoncausalityintheirproperhistoricalcontext.SincewhatItakethat contexttobedepartsfromthestandardviewinsigniï¬cantways,intheï¬rst part of this introduction I sketch the familiar contours of the standard view and present very general historiographical and historical reasons that show why we might consider rejecting central aspects of such a view. I also suggest that we can discern the main features of a more adequate account by approaching the topic in a fuller, contextualist manner. In the second part of this introduction I summarize each chapter in this book, illustrating how such an approach makes it possible to provide a more satisfying historical and philosophical account of Kantâ€™s central views on causality.